A general and atom-efficient continuous-flow approach to prepare amines, amides and imines via reactive N-chloramines - Jolley, Katherine E.; Chapman, Michael R.; Blacker, A. John (Beilstein Journal of Organic Chemistry, 2018)
Chloramines are an important class of reagents, providing a convenient source of chlorine or electrophilic nitrogen. However, the instability of these compounds is a problem which makes their isolation and handling difficult. To overcome these hazards, a continuous-flow approach is reported which generates and immediately reacts N-chloramines directly, avoiding purification and isolation steps. 2-Chloramines were produced from the reaction of styrenes with N-alkyl-N-sulfonyl-N-chloramines, whilst N-alkyl or N,N’-dialkyl-N-chloramines reacted with anisaldehyde in the presence of t-BuO2H oxidant to afford amides. Primary and secondary imines were produced under continuous conditions from the reaction of N-chloramines with base, with one example subsequently reduced under asymmetric conditions to produce a chiral amine in 94% ee.
Keywords: continuous flow; CSTR; N-chloramine; synthetic methods; telescoping